Russia’s Night Wolves Motorcycle Club: from 1%ers to political activists - Zabyelina, Yuliya (Trends in organized crime)
In the late 2000s, the Night Wolves Motorcycle Club, Russia’s largest motorcycle organization, became closely intertwined with the Kremlin’s domestic and international agendas, although only a decade ago they protested against the Soviet establishment and called for freedom and democracy. This article traces the ideological development of the Night Wolves, explores the nature of their relationship with theKremlin, and evaluates their role in President Vladimir Putin’s sistema—a system of governance grounded on informal mechanisms of power distribution and personalized loyalties. In addition, the article analyzes the activities of the Night Wolves in Ukraine and their role in the consolidation of pro-Russian forces and propagation of Kremlin-designed narratives.